'A patient act of adjustment': Subjectivisation, adjectives and Jane Austen. (August 2021) - González-Díaz, Victorina
Previous scholarship on Jane Austen has often commented on the moral overtones of her lexical choices; more specifically, the fact that "incorrect" lexical innovations and fashionable words (i.e. new usages) tend to be deployed as part of the idiolect of foolish, gullible or morally reprehensible characters. By contrast, ethically sound characters normally move within the limits of established ('old') usages and the "correct" Standard English repertoire. Taking the historical linguistic concept of subjectivisation as starting point, this case-study explores the use of two adjectives ( lovely and nice ) in Austen's novels. The article (a) demonstrates that a straightforward socio-moral classification of 'old' and 'new' word-senses in Austen's fiction is not fully adequate and (b) advocates, in line with recent scholarship, a more nuanced approach to the study of her fictional vocabulary, where old and new senses of a word (in this case, lovely and nice ) move across the idiolect of different character-types for ironic, character- and plot-building purposes.